Prevalence of Abortion and Contraceptive Practice among Women Seeking Repeat Induced Abortion in Western Nigeria - Mustafa Adelaja Lamina (Journal of Pregnancy)
Background. Induced abortion contributes significantly to maternal mortality in developing countries yet women still seek repeat induced abortion in spite of availability of contraceptive services. The aim of this study is to determine the rate of abortion and contraceptive use among women seeking repeat induced abortion in Western Nigeria. Method. A prospective cross-sectional study utilizing self-administered questionnaires was administered to women seeking abortion in private hospitals/clinics in four geopolitical areas of Ogun State, Western Nigeria, from January 1 to December 31 2012. Data were analyzed using SPSS 17.0. Results. The age range for those seeking repeat induced abortion was 15 to 51 years while the median age was 25 years. Of 2934 women seeking an abortion, 23% reported having had one or more previous abortions. Of those who had had more than one abortion, the level of awareness of contraceptives was 91.7% while only 21.5% used a contraceptive at their first intercourse after the procedure; 78.5% of the pregnancies were associated with non-contraceptive use while 17.5% were associated with contraceptive failure. The major reason for non-contraceptive use was fear of side effects. Conclusion. The rate of women seeking repeat abortions is high in Nigeria. The rate of contraceptive use is low while contraceptive failure rate is high.